CONSUMER REFERENCES TO CSR BY RETAIL COMPANIES: DOES IT AFFECT THEIR PURCHASING DECISION? - Noverinadyanda, Annisa Dhiya Ulhaq; Hariadi, Melia Femiola (Journal of Business and Management, 2018)
Abstract.Corporate Social Responsibility (CSR) is becoming the discussion topic and attention of many companies. CSR is one of considered as the company's interpretation communication to its stakeholders, including to their consumers. Therefore, CSR can be used as one of marketing strategy to attract consumers to be more interested in buying their products. This study intents to explore the extent Indonesian consumer perception toward CSR by retail companies and the effects of CSR to their purchasing decision, then collects primary data using qualitative approach method by conducting a semi-conducted interview to the specified sample. Using qualitative approach this study will interview around 22 people located in Indonesian urban area. The results indicate that Indonesians in urban areas aware about CSR, but some of them do not recognize the CSR program contained in retail companies due to lack of promotion and publicity. Consumer's positive perceptions of CSR by retail will influence its decision to purchase, especially when they are facing retail options to shop. Retails with CSR will tend to be selected instead of those without CSR. In other words, CSR can improve the company image. Positive corporate image through CSR can be a determinant of choice for consumer shopping in retail.Keywords: : CSR Awarness, CSR Perception, Purchasing Decision, Retail Company, Indonesia